Digitalisation of the cadastre. Development prospects in Russia and Belarus - Miroshnichenko, Olga I.; Diakonova, Anastasia V. (Journal of the Belarusian State University. Law, 2021)
The authors discuss the trends in the legal regulation of the land cadastre in the Russian Federation and the Republic of Belarus. Emphasis is placed on the long-term fruitful cooperation between the two countries. The conclusion is made about the obsolescence of the current law, about its inability to regulate new relations modified by the accelerating digitalisation, and about the need for a more rapid response to emerging challenges.